Longevity and health expectancy in an ageing society: implications for public health in Italy - Marianna Noale; Federica Limongi; Emanuele Scafato; Stefania Magg; Gaetano Crepaldi (Istituto Superiore di Sanità, 2012)
INTRODUCTION: While the prolongation of life expectancy is due to medical, economic, social and public health advancements, longevity may not necessarily be an indicator of real development. Epidemiologic data indicate, in fact, that advanced age carries the risk of multiple diseases, disability and loss of autonomy. MATERIALS AND METHODS: How the years gained are lived need to be assessed evaluating quality of life, health status, and disability. RESULTS AND CONCLUSIONS: Good health care planning should aim to ensure that the years of life gained are lived in good health conditions in the light of the World Health Organization's declaration that "increased longevity without quality of life is an empty prize. Health expectancy is more important than life expectancy".